On the interplay of shell structure with low- and high-frequency mechanics of multifunctional magnetic microbubbles - Poehlmann, Melanie; Grishenkov, Dmitry; Kothapalli, Satya V. V. N.; Harmark, Johan; Hebert, Hans; Philipp, Alexandra; Hoeller, Roland; Seuss, Maximilian; Kuttner, Christian; Margheritelli, Silvia; Paradossi, Gaio; Fery, Andreas (Soft Matter, 2014)
Polymer-shelled magnetic microbubbles have great potential as hybrid contrast agents for ultrasound and magnetic resonance imaging. In this work, we studied US/MRI contrast agents based on air-filled poly(vinyl alcohol)-shelled microbubbles combined with superparamagnetic iron oxide nanoparticles (SPIONs). The SPIONs are integrated either physically or chemically into the polymeric shell of the microbubbles (MBs). As a result, two different designs of a hybrid contrast agent are obtained. With the physical approach, SPIONs are embedded inside the polymeric shell and with the chemical approach SPIONs are covalently linked to the shell surface. The structural design of hybrid probes is important, because it strongly determines the contrast agent's response in the considered imaging methods. In particular, we were interested how structural differences affect the shell's mechanical properties, which play a key role for the MBs' US imaging performance. Therefore, we thoroughly characterized the MBs' geometric features and investigated low-frequency mechanics by using atomic force microscopy (AFM) and high-frequency mechanics by using acoustic tests. Thus, we were able to quantify the impact of the used SPIONs integration method on the shell's elastic modulus, shear modulus and shear viscosity. In summary, the suggested approach contributes to an improved understanding of structure-property relations in US-active hybrid contrast agents and thus provides the basis for their sustainable development and optimization. This journal is © The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20